Effects of the galactic magnetic field upon large scale anisotropies of extragalactic cosmic rays - Harari, Diego Dario (2010)
The large scale pattern in the arrival directions of extragalactic cosmic rays that reach the Earth is different from that of the flux arriving to the halo of the Galaxy as a result of the propagation through the galactic magnetic field. Two different effects are relevant in this process: deflections of trajectories and (de)acceleration by the electric field component due to the galactic rotation. The deflection of the cosmic ray trajectories makes the flux intensity arriving to the halo from some direction to appear reaching the Earth from another direction. This applies to any intrinsic anisotropy in the extragalactic distribution or, even in the absence of intrinsic anisotropies, to the dipolar Compton-Getting anisotropy induced when the observer is moving with respect to the cosmic rays rest frame. For an observer moving with the solar system, cosmic rays traveling through far away regions of the Galaxy also experience an electric force coming from the relative motion (due to the rotation of the Galaxy) of the local system in which the field can be considered as being purely magnetic. This produces small changes in the particles momentum that can originate large scale anisotropies even for an isotropic extragalactic flux.